Overexpression of RhoV Promotes the Progression and EGFR-TKI Resistance of Lung Adenocarcinoma - Chen, Hongjin; Xia, Ruixue; Jiang, Long; Zhou, Yong; Xu, Haojun; Peng, Weiwei; Yao, Chengyun; Zhou, Guoren; Zhang, Yijie; Xia, Hongping; Wang, Yongsheng (Frontiers in Oncology, 2021)
Background: The Rho GTPase family with 20 member genes play central roles in a wide variety of cellular processes and tumor cell migration and metastasis. Different Rho GTPase may play different roles in the progression of lung adenocarcinoma. Methods: We comprehensively examined the expression of all Rho GTPase family member genes in a panel of lung adenocarcinoma patient’s tumors and matched normal tissues. We next investigated the critical role of RhoV in different lung adenocarcinoma cells and animal models. Results: RhoV was identified as one of the most significantly overexpressed Rho GTPases in lung adenocarcinoma and associated with patients’ survival. Silencing RhoV expression inhibits proliferation, migration and invasion, and tumorigenicity capacities of lung adenocarcinoma cells. Moreover, knockdown RhoV promoted the sensitivity of EGFR-TKI in the gefitinib resistant PC9 cells (PC9-GR) and aggravated gefitinib-induced lung cancer cell apoptosis both in PC9 and PC9-GR cells. Our data also indicated that RhoV induced progression and EGFR-TKI resistance of lung adenocarcinoma may be related to the activation of the AKT/ERK pathway. Conclusion: Overexpression of RhoV in lung adenocarcinoma promotes the progression and EGFR-TKI resistance, suggesting RhoV is a promising prognosis and therapeutic target of lung adenocarcinoma.